The Girls of August - Siddons, Anne Rivers (New York : Grand Central Publishing, 2014)
Every August, four women gather together to spend a week at the beach, renting a new house each year. The ritual began when they were in their twenties and their husbands were in medical school. Their only criteria was oceanfront and isolation, their only desire to strengthen their far-flung friendships. They called themselves the Girls of August. But when one of the Girls dies tragically, the group slowly drifts apart. Years later, after a new marriage reunites them and they come together on a remote barrier island off the South Carolina coast, the women make startling discoveries that will change them in ways they never expected.
Keywords: Female friendship -- Fiction; Women -- Psychology -- Fiction; Beaches -- South Carolina -- Fiction; Vacation homes -- South Carolina -- Fiction; Vacation rentals -- South Carolina -- Fiction; Beaches; Female friendship; Vacation homes; Vacation rentals; Women -- Psychology; Death -- Fiction; Beaches -- South Carolina -- Fiction; South Carolina -- Fiction; South Carolina; Domestic fiction; Domestic fiction; Fiction; Domestic fiction; Domestic fiction